A Whole-Spine Radiography Study to Reduce Patient Exposure Dose and Artifacts Using the EOS Imaging System - DongHee Hong; YoungCheol Joo; Eunhye Kim (Bioengineering, 2024)
Whole-spine radiography can be accomplished through two methods: (1) segmented imaging employing X-ray tube angulation and detectors, or (2) the Euronext Paris Advanced Orthopedic Solutions (EOS) 2D Imaging system that can capture the entire spine in a single image using X-ray tubes and detectors oriented at a 90-degree angle. This study aimed to establish optimal EOS examination parameters based on patient morphotype and scan speed to reduce patient radiation exposure, repeat examinations, heat stress on equipment, and X-ray tube cooling time. X-ray exposure conditions involved adjustments of scan speed ranging from two to four steps, contingent upon the patient’s morphotype (‘S’, small body; ‘M’, medium body; and ‘L’, large body. Patient dose measurements were conducted 20 times for each set of conditions. When transitioning from an ‘S’ to an ‘M’ morphotype at a constant scan speed, the entrance skin dose (ESD) exhibited an increase of approximately 41.25 ± 4.57%. A similar change from an ‘M’ to an ‘L’ morphotype resulted in an ESD increase of roughly 59.56 ± 24.00%. A transition from an ‘S’ to an ‘L’ morphotype at the same scan speed manifested an ESD elevation of approximately 124.21 ± 26.96%. This study underscores significant variations in radiation dose, ranging from 40% to 50%, when altering morphotype while maintaining a consistent scan speed.